Effect of Dominance Hierarchy and Lameness On the milk production in Friesian-cows - جبور, زهير; سلهب, محمد; محمد, سمر (Latakia University Journal -Biological Sciences Series, 2020)
The aim of this study was to assess the stress caused by dominance hierarchy and lameness, and its effect on the amount of milk produce. Two herds of cows were observed , the first included cows of similar ages and the second included cows of different ages. The results showed that , neutral cows produced the most milk in both herds . a significant decrease was observed in the average milk associated with increase degree of lameness , and significant differences was observed between the mean quantities of milk and the dominance ranks in two herds (P<0.05). The results, according to spearman and person tests ,showed a negative significant correlation between lameness and the average amount of milk produced .